Effect of the size of tympanic membrane perforation on hearing - Farouk Al- Omari, Alyaa; S.Al-Doski, Fadhila (Tikrit Journal of Pharmaceutical Sciences, 2023)
Tympanic membrane (TM) perforation is one of the most common causes of hearing impairment. Apart from conduction of sound waves across the middle ear, the tympanic membrane, also sub-serves a protective function to the middle ear cleft and round window niche. It has been established that the larger the perforation on the tympanic membrane, the greater the decibel loss. The aim of this study is to determine the effect of the size of the tympanic membrane perforation on hearing. The study was conducted at Al-Jumhoori teaching hospital during march 2011 to march 2012. Seventy-eight patients with perforated tympanic membranes were included in the study.They all have TM perforation due to recurrent or chronic otitis media. Patients with traumatic TM perforation were excluded from the study. There were 47 males (46.5%) and 54 females (53.5%). Twenty patients had left ear perforation, 35 patients had right ear perforation, and 23 patients had bilateral perforations. Each ear was taken as a case, so the total number of the perforated ear drums were 101. The age ranged from 13- 56 with the mean of (31.64 ± 13.249) years. The TM perforation was examined and photo image was taken with the aid of the endoscope, and the percentage of the perforation was measured from the whole area by using a special Microsoft (infomap). Controls were 55 patients with a mean age 30.73 ±12.09( range 14-53) years. Male controls were 34 (61.8%), and 21 female controls(38.2%). There was a highly significant correlation between size of TM perforation with the hearing level, air bone gap, high frequency hearing loss and low frequency hearing loss. As a conclusion, there is strong relationship between the size of TM perforation and the hearing level, air-bone gap and both the low frequency and the high frequency hearing level and air-bone gaps.